Techno-Economic Analysis of Solar Thermal Hydrogen Production in the United Arab Emirates - Abdulrahman Joubi; Yutaro Akimoto; Keiichi Okajima (Hydrogen, 2022)
Solar thermal technology can provide the United Arab Emirates and the Middle East region with abundant clean electricity to mitigate the rising levels of carbon dioxide and satisfy future demand. Hydrogen can play a key role in the large-scale application of solar thermal technologies, such as concentrated solar plants, in the region by storing the surplus electricity and exporting it to needed countries for profit, placing the Middle East and the United Arab Emirates as major future green hydrogen suppliers. However, a hydrogen supply chain comparison between hydrogen from CSP and other renewable under the UAE’s technical and economic conditions for hydrogen export is yet to be fully considered. Therefore, in this study we provide a techno-economic analysis for well-to-ship solar hydrogen supply chain that compares CSP and PV technologies with a solid oxide water electrolyzer for hydrogen production, assuming four different hydrogen delivery pathways based on the location of electrolyzer and source of electricity, assuming the SOEC can be coupled to the CSP plant when placed at the same site or provided with electric heaters when placed at PV plant site or port sites. The results show that the PV plant achieves a lower levelized cost of electricity than that of the CSP plant with 5.08 ¢/kWh and 8.6 ¢/kWh, respectively. Hydrogen production results show that the scenario where SOEC is coupled to the CSP plant is the most competitive scenario as it achieves the payback period in the shortest period compared to the other scenarios, and also provides higher revenues and a cheaper LCOH of 7.85 $/kgH2.